A Bibliometric Analysis of the Quantitative Mental Health Literature in Occupational Therapy. (2nd October 2018) - Gutman, Sharon A.; Brown, Ted
ABSTRACT: A bibliometric analysis was performed to examine the impact and use of the peer-reviewed occupational therapy intervention effectiveness literature addressing adults with mental illness, 2000–2016. Of 2, 597 articles, 68 were quantitative studies assessing an intervention for adults with mental illness. These studies had a collective citation count of 1, 455 and were published in 29 journals in 14 countries. The majority ( n = 36; 52.94%) were randomized controlled and two-group controlled studies. The most commonly assessed interventions were life skills and community reintegration ( n = 20, 29.41%) and supported employment ( n = 16, 23.52%). Sixty-five (95.58%) studies found statistically significant results on the primary or secondary outcomes.